Stigma and Quality of Life Among Pre-elderly with HIV in Jakarta, Indonesia - Pakpahan, Evanina Alice; Surilena, Surilena; Hardi, Nicholas (Althea Medical Journal, 2025)
Background: The quality of life (QoL) of people living with HIV (PLWHIV) is affected by physical, psychological, social, and spiritual aspects. During the pre-elderly period (ages 45–59 years), these aspects become major challenges. Stigma is one of the social aspects that may be related to QoL among PLWHIV. This study aimed to examine the correlation between stigma and QoL among pre-elderly with HIV.Method: This was an analytical observational study with a cross-sectional design, conducted from July 2022 to August 2023 in health services and online-based HIV communities in Jakarta, Indonesia. Sampling was performed using convenience sampling, including 120 pre-elderly living with HIV. Data were collected online using Google Forms. Stigma was assessed using the Berger HIV Stigma Scale, while QoL was measured using the WHOQOL-HIV BREF questionnaire. Data were analyzed using Spearman’s rank correlation test in SPSS.Results: Most participants were male (62.5%). The highest median scores in stigma domains were public attitudes (41) and personalized stigma (36). For QoL, the highest median scores were in the physical and spiritual domains (both 15). Personalized stigma and disclosure concerns were negatively correlated with the physical, psychological, independence, and spiritual QoL domains (p<0.05). Negative self-image demonstrated negative correlations with all QoL domains (p<0.05).Conclusions: Stigma is negatively correlated with the quality of life among pre-elderly with HIV in Jakarta. The greater the stigma experienced, the lower their quality of life. Further research using qualitative methods such as in-depth interviews, is recommended to explore the correlation of each stigma domain with the quality of life.